The many forms of school violence: A singular state of art in the Colombian context (Quaestiones Disputatae: temas en debate, 2017)
Reflecting on school violence in Colombia is not just a purely academic exercise,but also gives rise to an urgent need for an immediate approach to tackle it, asit involves society, our children, teachers and the community in general.On the other hand, there is a phenomenon that connects the violence that ourcountry has historically suffered and the violence that has managed to permeatethrough our educational centers, classrooms, physical and virtual spaces, suchas social networks. From this point of view, we try to review the issue taking into account the different efforts that are being made at the international and national levels. We consider the various underlying facets of school violence, which are worthy of study and give us a more integrative and hermeneutic view of the problem in order to finally face the national reality, as a representative element that helps us at this time when we are imagining a country in peace.
Keywords: armed conflict; education; peace; school violence; society